Assessment of the nutrition environment in rural counties in the Deep South - Shikany, James M. (J Nutr Sci, 2018)
The nutrition environment, including food store type, may influence dietary choices, which in turn can affect risk of obesity and related chronic diseases such as CHD, diabetes and cancer. The objective of the present study was to elucidate the extent to which healthy foods are available and affordable in various rural food outlets. A subset of the nutrition environment was assessed using the Nutrition Environment Measures Survey in Stores (NEMS-S). The NEMS-S instrument assessed the availability and price of healthy foods (e.g. low-fat/non-fat milk, lean meats and reduced-fat dinner entrées) compared with less healthy counterparts (e.g. whole milk, non-lean meats and regular dinner entrées). The NEMS-S also assessed the quality of fresh fruits and vegetables. Availability, prices and quality of healthy foods were compared between grocery stores (n 24) and convenience stores (n 67) in nine rural counties in Alabama. Mean availability subscale score (possible range 0 to 30; higher score indicates a greater number of healthier foods were available) for grocery stores was 22·6 (sd 8·1), compared with 6·6 (sd 5·2) in convenience stores (P < 0·0001); and mean price subscale score (possible range −9 to 18; higher score indicates that healthier options were less expensive than the less healthy options) for grocery stores was 2·4 (sd 2·7), compared with 0·7 (sd 1·2) in convenience stores (P = 0·0080). Mean total NEMS-S score (possible range −9 to 54) in grocery stores was 29·8 (sd 10·9) compared with 7·3 (sd 7·1) in convenience stores (P < 0·0001). Both grocery and convenience stores could be strategic points of intervention to improve the nutrition environment in the counties that were surveyed.